An Experimental Study on the Impact of Collaborative and Active Learning on Vocational Students' Learning Achievement and Self-Motivation (GIST – Education and Learning Research Journal, 2024)
The study examines a blended instructional approach combining collaborative and active learning to improve vocational students' learning achievement and self-motivation. An experimental design was utilized, dividing vocational students into control and experiment groups. The experiment group participated in a one-month collaborative and active learning intervention, while the control group received traditional instruction. The experiment group achieved significant gains in academic achievement, with pre-test and post-test means rising from 79.63 to 86.15 (t=19.72, p